Humen security in pakistan - Khan, Ehsan Mehmood ([S.l.] : Narratives (Pvt) Ltd., 2013)
Traditional state security came under debate soon after the end of the Cold War. An alternative concept of human security grew quickly in academic and policy circles around the world, both horizontally and vertically. Even as debate continues, a number of countries have already taken the lead in implementing a holistic consideration of their socio-security and politico-economic environment. Nevertheless, the concept of human security is neither well understood in Pakistan at conceptual and academic level nor implemented in a coherent form at the policy level. This book presents an objective evaluation of the concept, besides an honest analysis of Pakistan$1 (Bs human security profile. Thus, it not only contributes to the conceptual debate on human security but analyzes the human security profile of Pakistan for the purpose of offering policy recommendations. The book is expected to interest Pakistani students, scholars, security experts and policy planners, as well as foreign readers desiring to know more about the concept of human security as applied to a specific case, Pakistan. Being a conceptual and academic book, it is recommended for inclusion in curricula at university level for the social sciences disciplines, security, strategy, international relations, political science and history.s
Kindle eBook.